Comparing perceptual signals of single V5/MT neurons in two binocular depth tasks. - Krug, K; Cumming, BG; Parker, A (2004)
Neurons in the extrastriate visual area V5/MT show perceptually relevant signals in binocular depth tasks, which can be measured as a choice probability (CP) for the neuron. The presence of a CP in a particular paradigm may be an indicator that the neuron is generally part of the substrate for the perception of binocular depth. We compared the responses of those single neurons that show CPs in one stereoscopic depth task with their responses in another stereo task. Each neuron was tested for the presence of 1) CPs during a task in which macaques responded to the sign of binocular depth in a structure-from-motion stimulus, to judge its direction of three-dimensional rotation and 2) a consistent response to the stereo disparity of binocularly anti-correlated stimuli. Previous work, confirmed here, shows that changing the disparity of these binocularly anti-correlated stimuli often fails to yield a coherent change in the depth percept. For each test alone, there are V5/MT neurons that carry signals that are congruent with the perceptual effects. However, on comparing tests, there is no fixed pool of neurons that can account for the binocular depth percept. Excitation of neurons with a measurable CP does not necessarily lead to a change in perception. The cortical circuitry must be able to make dynamic changes in the pools of neurons that underlie perceptual judgments according to the demands of the task.